2014
DOI: 10.1177/1359105314542817
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of DVD, telephone, and usual care for increasing mammography adherence

Abstract: The purpose of this study was to test an intervention to increase mammography screening in women ages 51 to 75 who had not received a mammogram in the last 15 months. A total of 1681 women were randomized to: 1) a mailed tailored interactive DVD, 2) a computer-tailored telephone counseling, or 3) usual care. Women with incomes below $75,000 who were in the interactive DVD group had significantly more mammograms than women in usual care. Women with incomes above $75,000 had significantly fewer mammograms than w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…Indeed, previous studies have shown that mere measurement may promote health behaviors(25), and a number of randomized intervention trials have found changes in cancer screening outcomes among individuals in comparison groups who completed data collection but did not receive tailored interventions. (16;26;27)…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies have shown that mere measurement may promote health behaviors(25), and a number of randomized intervention trials have found changes in cancer screening outcomes among individuals in comparison groups who completed data collection but did not receive tailored interventions. (16;26;27)…”
Section: Discussionmentioning
confidence: 99%
“…Although tailored interventions are efficacious, most studies have not tailored on a comprehensive set of variables that include baseline stage of change, demographics, and belief variables (22,23). With rapid advances in technology, our ability to develop phone or Web-based messages tailored to a larger set of variables is possible.…”
Section: Introductionmentioning
confidence: 99%
“…The good news is that regular mammography screening can help to reduce mortality. Champion et al (2014) did a Computer and Phone (CAPE) study including two tailored intervention methods, mailed DVD (abbreviated as DVD) and telephone counseling (abbreviated as TC). A CAPE randomized controlled trial was conducted to determine whether the two interventions were more efficacious than the usual care (abbreviated as UC) method at promoting mammography screening among women who are non-adherent to breast cancer screening guidelines at baseline.…”
Section: Discussionmentioning
confidence: 99%